A new approach for the ortho-positronium lifetime determination in a vacuum cavity. (November 2018) - Vigo, C.; Raaijmakers, M.; Gerchow, L.; Radics, B.; Rubbia, A.; Crivelli, P.
Abstract: Currently, the experimental uncertainty for the determination of the ortho-positronium (o-Ps) decay rate is at 150 ppm precision; this is two orders of magnitude lower than the theoretical one, at 1 ppm level. Here we propose a new proof of concept experiment aiming for an accuracy of 100 ppm to be able to test the second-order correction in the calculations, which is ≃ 45 ( a π ) 2 ≈ 200 ppm . The improvement relies on a new technique to confine the o-Ps in a vacuum cavity. Moreover, a new method was developed to subtract the time dependent pick-off annihilation rate of the fast backscattered positronium from the o-Ps decay rate prior to fitting the distribution. Therefore, this measurement will be free from the systematic errors present in the previous experiments. The experimental setup developed for our recent search for invisible decay of ortho-positronium is being used. The precision will be limited by the statistical uncertainty, thus, if the expectations are fulfilled, this experiment could pave the way to reach the ultimate accuracy of a few ppm level to confirm or confront directly the higher order QED corrections. This will provide a sensitive test for new physics, e.g. a discrepancy between theoretical prediction and measurements could hint at the existence of a hidden sector which is a possible dark matter candidate.